Carbon encapsulated hybrid Fe-based nanostructure with durable lithium storage. Issue 11 (27th February 2023) - Chen, Xiaoyun; Shi, Xiaomeng; Cheng, Mingren; Zhang, Mengzhen; Ma, Jiamin; Liang, Zhong; Zhai, Xinyun; Du, Yaping
Abstract : N-doped carbon coated Fe3 O4 was synthesized from MIL-53(Fe) coated PDA as a precursor and used as an anode material for LIBs. Abstract : Recently, metal organic framework (MOF) derived electrode materials have been widely studied. A large contact area on the electrode/electrolyte interface can be provided by the porous structure of MOFs, which is beneficial for promoting the mass transfer and buffering volume changes during long time cycling. In this work, MIL-53(Fe) coated with polydopamine (PDA) derived Fe3 O4 @N-doped carbon hybrid material (Fe3 O4 @NC) with a polyhedron morphology was synthesized. The porous encapsulation structure with well-connected carbon networks inside and excellent electrolyte contact interfaces outside is beneficial to ion intercalation and the stability of the solid electrolyte interface (SEI) layer, respectively. As an anode material, porous Fe3 O4 @NC nanorods exhibited a specific capacity up to 750 mA h g −1 after 700 cycles at a high current density of 0.5 A g −1 and high-rate capability of 272 mA h g −1 at 5 A g −1 . Moreover, FeS2 @NC (Fe3 O4 derived FeS2 with PDA derived carbon coating) was also synthesized to demonstrate the possibility of modification on electrode materials. This work provides an effective design scheme for improving electrochemical performances of MOF-derived electrode materials and presents a general fabrication strategy for the synthesis of other energy storage and conversion materials.